Gen Z’s Impulse Buying Behavior of Skincare Product: The Role of FOMO, Celebrity Endorser and Hedonism - Shaumi Ramadhani; Kartika Anggraeni Sudiono Putri (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
Fear of Missing Out (FOMO) is a phenomenon that is currentlyprevalent among Generation Z in the form of fear of being leftbehind with the experiences felt by their social environment, whichoften triggers impulse buying behavior to stay on trend. The purpose of this study was to analyze the relationship between Fearof Missing Out (FOMO) and celebrity endorsers on impulsivebuying with hedonism as a mediating variable. This quantitativeresearch uses a correlational approach with data collectiontechniques by means of a survey through distributing questionnairesin the form of google forms to Generation Z consumers of skincareproducts in Malang City. The study employed a non probabilitysampling approach, specifically using a purposive sampling method, and included a total of 110 respondents as the sample. Thisstudy analyzed the data using the Partial Least Squares StructuralEquation Modeling (PLS-SEM) technique, utilizing SmartPLSsoftware version 3. SmartPLS version 3 software.The results showedthat FOMO affects impulsive buying in Generation Z consumers ofskincare products in Malang City both directly and indirectlythrough hedonism as mediation. Meanwhile, celebrity endorsers donot directly affect impulsive buying in Generation Z consumers ofskincare products in Malang City, but indirectly through hedonismas mediation. In addition, hedonism affects impulsive buying in Generation Z consumers of skincare products in Malang City.